The Examining the Structural and Technical Characteristics of the Water Buffalo Farms in Sivas Province from the Perspective of Animal Welfare: The Structural and Technical Characteristics of the Water Buffalo Farms - Özdemir, G (Journal of the Hellenic Veterinary Medical Society, 2023)
In Turkey, water buffalo husbandry is conducted generally by using the traditional methods in shelters designed for cattle. The present study reports the data of the items of a questionnaire, which was conducted with 122 water buffalo breeders which are located in Central, Şarkışla, and Suşehri districts of Sivas province, regarding the structural and technical aspects of shelters such as shelter location, shelter type, building material, ventilation, and lighting. It was determined that, among the water buffalo breeders in Sivas province, the shelters were generally (73.5%) located nearby the house, that the building materials used in construction of the shelters were stone in 55.4%, concrete in 21.5% and briquette in 16.5% (p<0.0001), and that the floor materials used were concrete in 99.2% (p<0.05), whereas the roofing material was sheet metal/eternit in 80% (p<0.0001). It was found that water buffalos and cattle were held together in closed tethered systems (95.8%) and the space needs of animals were met by using chains having 40-60cm in length (63.1%). In conclusion, considering the animal welfare and behaviors, it was concluded that the infrastructural improvements to ensure the standardization in water buffalo shelters should be prioritized, that the old shelters should be re-organized, and that the watering systems in shelters should be analyzed.